2012
DOI: 10.1177/1359105312439734
|View full text |Cite
|
Sign up to set email alerts
|

Warning labels formulated as questions positively influence smoking-related risk perception

Abstract: Research on warning labels printed on cigarette packages has shown that fear inducing health warnings might provoke defensive responses. This study investigated whether reformulating statements into questions could avoid defensive reactions. Smokers were presented with either warning labels formulated as questions, textual warning labels, graphic warning labels, or no warning labels. Participants' smoking-related risk perception was higher after exposure to warning labels formulated as questions or no warning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 49 publications
6
65
0
1
Order By: Relevance
“…Messages that are structurally novel have been shown to provoke thoughtful action (Berlyne, 1971;Langer & Abelson, 1972;Langer, Blank, & Chanowitz, 1978). Research on persuasion has shown that when individuals generate arguments and conclusions themselves, these are more convincing than statements provided by external sources (Glock, Müller, & Ritter, 2013). This is likely as individuals tend to trust themselves and selfgenerated arguments are often perceived as more accurate than information provided by external sources (Hoch & Deighton, 1989;Levin, Johnson, & Chapman, 1988;Mussweiler & Neumann, 2000).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Messages that are structurally novel have been shown to provoke thoughtful action (Berlyne, 1971;Langer & Abelson, 1972;Langer, Blank, & Chanowitz, 1978). Research on persuasion has shown that when individuals generate arguments and conclusions themselves, these are more convincing than statements provided by external sources (Glock, Müller, & Ritter, 2013). This is likely as individuals tend to trust themselves and selfgenerated arguments are often perceived as more accurate than information provided by external sources (Hoch & Deighton, 1989;Levin, Johnson, & Chapman, 1988;Mussweiler & Neumann, 2000).…”
Section: Literature Reviewmentioning
confidence: 96%
“…In a college-aged setting, warning labels contradicting positive outcome expectancies as used in this study [48] as well as health-related warning labels formulated as questions turned out to be effective when it comes to short term smoking behaviour, as first results show [60]. However, although college-aged smokers are at risk to become heavy smokers [61,62], they show different smoking patterns than older smokers [63].…”
Section: Discussionmentioning
confidence: 81%
“…As our study demonstrates an increased efficacy of self-persuasion when consumers are highly involved, self-persuasion may be most effective when applied to high-involvement products, such as holidays, cars and insurances (Percy and Donovan, 1991). In addition, as it has been demonstrated that self-persuasion is also very effective in a mass-media context by framing arguments as questions and presenting these questions to an audience (Glock et al, 2013;Müller et al, 2016), self-persuasion may even be considered to be a means for mass media campaigning or advertising. For instance, with phrases like "Fun, anyone?"…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has since shown that it is not necessary to write down arguments to induce self-persuasion; an easily applicable method to induce self-persuasion is asking questions, which triggers people into coming up with arguments (Loman et al, 2015), a process which is assumed to be automatic (Fitzsimons and Williams, 2000). Several studies have demonstrated that merely presenting participants with questions (rather than statements) about why smoking is bad led to a higher smoking-related risk perception (Glock et al, 2013) and longer absence rates (Müller et al, 2016). In relation to other health-related behaviors, formulating questions instead of statements has been shown to lead to an increase in negative outcome expectancy perception (Krischler and Glock, 2015), lower alcohol consumption rates (Loman et al, 2015) and an increase in exercise behavior (Williams et al, 2006;for negative side-effects, however, see, Fitzsimons and Moore, 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation